NetFPGA: status, uses, developments, challenges, and evaluation (2020)
The constant growth of the Internet, driven by the demand for timely access to data center networks; has meant that the technological platforms necessary to achieve this purpose are outside the current budgets. In this order to make and validate relevant, timely and relevant contributions; it is necessary that a wider community, access to evaluation, experimentation and demonstration environments with specifications that can be compared with existing networking solutions. This article introduces the NetFPGA, which is a platform to develop network hardware for reconfigurable and rapid prototyping. It’s introduces the application areas in high-performance networks, advantages for traffic analysis, packet flow, hardware acceleration, power consumption and parallel processing in real time. Likewise, it presents the advantages of the platform for research, education, innovation, and future trends of this platform. Finally, we present a performance evaluation of the tool called OSNT (Open-Source Network Tester) and shows that OSNT has 95% accuracy of timestamp with resolution of 10ns for the generation of TCP traffic, and 90% efficiency capturing packets at 10Gbps of full line-rate.